How parents can help or hinder access to mental health services for young people. (February 2023) - Platell, Monique; Cook, Angus; Martin, Karen
Highlights: Examining adolescent perceptions of their parents influence on their access and use of mental health services. Use qualitative face to face interviews. Parents were highlighted by adolescents as prominent influences in adolescent mental health journeys, however this influence could be positive and negative for the adolescent. Highlights the complexity of the involvement of parents in their child's mental health service use. Abstract: Aim: To explore adolescent experiences of accessing and utilising mental health service in Perth, Western Australia. This paper focusses on the adolescent identified influence of parents in accessing and using mental health services. Method: Qualitative semi-structured face-to-face interviews with 22 adolescents aged 14–18 years old in Perth, Western Australia. Interviews were transcribed verbatim and analysed thematically. Results: The influence of parents on adolescents' experiences within the mental health system were grouped under three themes: parental involvement in accessing and continued use of mental health services for their children; parental understanding and awareness of child's mental health problems; parent–child relationship. It was common for adolescents to report that the influence and involvement of their parents could create facilitators and barriers to mental health care. Conclusion: This research highlighted the complexities in how parents can be both supportive and hindering influences in their child's mental health care. Adolescent experiences highlight the need for parents to be a key area of focus for mental health services and future reforms to support and improve adolescent mental health service use. Additional research is needed to explore how to effectively increase parental mental health literacy in the community and what factors are needed to create trusted parent-adolescent relationships.